The Review of Sound-based Steganographic Techniques - Harbarchuk, V.; Kozieł, G. (Інститут проблем штучного інтелекту МОН України та НАН України, 2008)
The review of steganographic sound-based methods developed in the last ten years are presented in this article. The methods are grouped according to the domain of embedding the hidden information. The requirements introduced by phonographic industry were presented too.